2013
DOI: 10.1542/peds.2012-0517
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of LCPUFA Supplementation of Infant Formula and Visual Acuity

Abstract: Current evidence suggests that LCPUFA supplementation of infant formulas improves infants' visual acuity up to 12 months of age.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
57
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(67 citation statements)
references
References 47 publications
0
57
0
3
Order By: Relevance
“…A meta-analysis of 15 randomized studies on the effects of LC-PUFA supplementation in term infants did not show significant beneficial effects of supplementation on either mental or psychomotor development [82]. This finding was repeated in another meta-analysis including 12 trials involving 1,802 infants and demonstrating no significant effect of LC-PUFA supplementation of formula on early infant visual development and cognition [83,84]. Outcomes regarding visual acuity were inconsistent: no overall benefits were reported in a Cochrane review, with 5 out of 9 studies not showing a beneficial effect [82].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A meta-analysis of 15 randomized studies on the effects of LC-PUFA supplementation in term infants did not show significant beneficial effects of supplementation on either mental or psychomotor development [82]. This finding was repeated in another meta-analysis including 12 trials involving 1,802 infants and demonstrating no significant effect of LC-PUFA supplementation of formula on early infant visual development and cognition [83,84]. Outcomes regarding visual acuity were inconsistent: no overall benefits were reported in a Cochrane review, with 5 out of 9 studies not showing a beneficial effect [82].…”
Section: Resultsmentioning
confidence: 99%
“…Outcomes regarding visual acuity were inconsistent: no overall benefits were reported in a Cochrane review, with 5 out of 9 studies not showing a beneficial effect [82]. In contrast, a meta-analysis involving 1,949 infants from 19 studies found a significant benefit for infants' visual acuity after LC-PUFA supplementation up to 12 months of age [83]. Studies that provided higher doses of DHA (at least 0.32% in formula) and AA (at least 0.65% in formula) for a longer duration (>1 year) and measured visual acuity with electrophysiological tests were more likely to show beneficial effects of supplementation in term infants [82].…”
Section: Resultsmentioning
confidence: 99%
“…However, some controversy remains with regards to the effects of the supply of preformed LC-PUFA on neurodevelopment of healthy term infants. For example, the authors of a meta-analysis on randomized trials evaluating infant formula with LC-PUFA compared to formula without LC-PUFA concluded that while some studies showed a significant benefit, overall no significant effect was detectable [37,38] . The authors noted the limitation of their conclusions by a large degree of heterogeneity of the included studies, which provided markedly different interventions and also used a variety of very different outcomes and approaches to outcome assessment.…”
Section: Long-chain Polyunsaturated Fatty Acidsmentioning
confidence: 99%
“…In addition, the effects of oral supplementation of omega-3 fatty acids during pregnancy on early childhood development, especially visual, were inconclusive (Gould et al 2013). In a meta-analysis of 12 studies (1949 infants up to 12 months of age), omega-3 supplementation of infant formulas appeared to have possible effects on visual acuity as measured by evoked potential for infants 2 months of age and by behavioral methods at 12 months (Qawasmi et al 2013). In another meta-analysis conducted by the same authors evaluating the effects of omega-3 supplementation of infant formula, no effects on general cognition were identified (Qawasmi et al 2012).…”
Section: Neurological Developmentmentioning
confidence: 99%